Knowledge of atorvastatin and associated factors on knowledge among the patients with ischemic heart disease at Teaching hospital, Jaffna, Sri Lanka - Kodelinishiya, A.; Kowsika, K.; Yathusha, K.; Thuvaragan, S.; Guruparan, M. (Faculty of Allied Health Sciences, University of Jaffna, Sri Lanka, 2023)
Introduction: Ischemic heart disease is the leading cause of hospital deaths in Sri Lanka, which accounts for 14.1% of all cases. Statins reduce the risk of developing atherosclerosis among patients with ischemic heart diseases. Adequate knowledge on medicines will improve the adherence and thus therapeutic outcomes. Objective: To assess the knowledge of atorvastatin and associated factors among the patients with ischemic heart disease at the Teaching hospital, Jaffna. Methodology: A descriptive cross-sectional study was conducted among 430 patients with ischemic heart disease using systematic random sampling technique. An interviewer-administered questionnaire was used to collect data. The 11 items knowledge questionnaire included dose, frequency, side effects, and purpose of usage. Knowledge on atorvastatin was categorised as adequate and inadequate with the cut-off value of 50% of the total knowledge score. The Chi-Square test was used to assess the association between variables at the 95% confidence interval and P value less than 0.05 was considered as a significant level. Data was analysed using SPSS version 25. Ethical clearance was obtained from the Ethics Review Committee, Faculty of Medicine, University of Jaffna. Results: The response rate was 96.51% (N=430). More than half of the patients (63%) had adequate knowledge on atorvastatin. Gender (p=0.013), level of education (p=0.044), occupation (p=0.026) and having side-effects (p=0.002) had significant association with knowledge. However, age, marital status, ethnicity, monthly income, duration of treatment, lifestyle modification, usage of traditional medicine and clinic visit did not associate with knowledge on atorvastatin. Patients have more knowledge on purpose of statin usage (70%), frequency (86.7%) and miss dose of statins (97.4%). Most of the patients had poor knowledge about the name of statin (27.9 %) and their dose (28.8%) need of prescription for purchasing statins (2.8%). Conclusion: Knowledge on atorvastatin among patients with ischemic heart disease was adequate among more than half of the patients. More attention needs to be taken to improve the knowledge especially among females, patients studied up to O/L, nonemployees and patients having side effects. Pharmacists could play a role in educating patients by providing counselling to improve their knowledge.
Keywords: Knowledge; Atorvastatin; Ischemic heart disease